Potensi Ekstrak Daun Tembelekan Lantana camara sebagai Penghambat Tumbuh Bakteri pada Rumput Laut Kappaphycuz alvarezii Potency of Leaf Extract Tembelekan Lantana camara as Bacteria Growing Inhibitor on Seaweed Kappaphycuz alvarezii - Tolanamy, Emand Syapriawan; Patadjai, Rahmad Sofyan; Nur, Inriyani (Jurnal Sains dan Inovasi Perikanan / Journal of Fishery and Innovation (JSIPi), 2017)
ABSTRACT One of the main obstacles in the effort to increase production of seaweed culture, especially of the species Kappaphycus alvarezii is a change in the quality of water environment and very high intensity of seaweed diseases. The aims of this study is to test the ability of tembelekan Lantana camara leaf extract in preventing and reducing the rate of disease-causing bacteria transmission in the seaweed thallus by in vitro and cohabitation methods. The results showed tembelekan leaf extract solution with a concentration of 2000 ppm can inhibit the growth of Vibrio alginolyctus bacteria cause ice-ice by in vitro method. Submersion treatment for 60 minutes was able to suppress the ability of pathogens transmitting than submersion for 30 and 90 minutes by cohabitation method. Key words: Kappaphycus alvarezii, Lantana camara, Vibrio alginolyctus, ice-ice disease. ABSTRAK Salah satu kendala utama dalam upaya peningkatan produksi budidaya rumput laut terutama dari jenis Kappaphycus alvarezii adalah perubahan kualitas lingkungan perairan dan intensitas serangan penyakit rumput laut sangat tinggi. Penelitian ini bertujuan menguji kemampuan larutan ekstrak daun tembelekan Lantana camara dalam mencegah dan mengurangi tingkat transmisi bakteri penyebab penyakit ice-ice pada thallus rumput laut K. alvarezii secara in vitro dan kohabitasi. Hasil penelitian menunjukkan larutan ekstrak daun tembelekan dengan konsentrasi 2000 ppm dapat menghambat pertumbuhan bakteri Vibrio alginolyctus penyebab ice-ice secara in vitro. Perlakuan perendaman selama 60 menit lebih mampu menekan kemampuan transmisi bakteri patogen pada pengujian secara kohabitasi dibandingkan perendaman selama 30 dan 90 menit. Kata Kuncis: Kappaphycus alvarezii, Lantana camara, Vibrio alginolyctus, penyakit ice-ice.